Respostas

2014-01-24T18:50:57-02:00
Letra a : 

x²-x-20=0 ~> a = 1 , b = -1 , c = -20

Δ = b² - 4ac
Δ = (-1)² - 4.1.(-20)
Δ = 1 - (-80)
Δ = 81

x = - b 
± √Δ
          2a

x = - (-1) ± √81
            2.1

x = ± 9
         2

x' = 1 + 9  = 10 = 5               x" = 1 - 9 = -8 = -4
          2        2                               2       2


Letra b : 

x²-3x-4=0 ~> a = 1 , b = -3 , c = -4

Δ = b² - 4ac
Δ = (-3)² - 4.1.(-4)
Δ = 9 - (-16)
Δ = 25

x = -b ± √Δ
         2a

x = -(-3) ± √25
          2.1

x = ± 5 
        2

x' = 3 + 5 = 8 = 4                     x" = 3 - 5 = -2 = -1
         2       2                                    2       2

3 5 3